L'autonomie à l'école maternelle : un nouvel idéal pédagogique ? - Christophe Joigneaux (Nantes Université, 2014)
What are the implications of the dissemination of autonomy model to kindergarten? Because they seem premature at this level of education, its practices particularly enlighten the "civilizing process" that underlies it, based both on reflexivity and the remote control that authorizes writing. But the diversity of practices in the classrooms of this new form of government, in Foucault's sense, leads to the conclusion that it is a socio-educational inequality generator. Indeed, it seems that it can be both normalizing for some students and emancipation for others, depending on their predisposition to use the cognitive powers of writing.